2020
DOI: 10.3390/cryst10040274
|View full text |Cite
|
Sign up to set email alerts
|

Wide Angle X-Ray Scattering to Study the Atomic Structure of Polymeric Fibers

Abstract: Natural fibrillar-like macromolecules find applications in several fields, thanks to their peculiar features, and are considered perfect building blocks for natural and artificial functional materials. Indeed, fibrous proteins (such as collagen or fibroin) are commonly used in scaffold fabrication for biomedical applications, due to the high biophysical similarity with the extracellular matrix (ECM) which stimulates tissue regeneration. In the textile industry, cellulose-based fabrics are widely used in place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Despite of this, it can attain significant performance even in this case by reducing the noise level as witnessed by the measured values of the peak signal-to-noise ratio and of the structure similarity. In particular, we showed that an improvement in the values of the PSNR and of the SSIM can be obtained when considering also the source term (β = 0) in Equation (2). The parameter β is the only free parameter that has to be tuned to obtain the better performance of the method.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite of this, it can attain significant performance even in this case by reducing the noise level as witnessed by the measured values of the peak signal-to-noise ratio and of the structure similarity. In particular, we showed that an improvement in the values of the PSNR and of the SSIM can be obtained when considering also the source term (β = 0) in Equation (2). The parameter β is the only free parameter that has to be tuned to obtain the better performance of the method.…”
Section: Discussionmentioning
confidence: 92%
“…The study of the properties of crystalline materials mainly relies on the use of X-ray diffraction (XRD) techniques, which give relevant information for several applications as, for example, in nanotechnology [1,2]. The processing of such data requires a chain of preliminary steps aiming at improving the quality of XRD data [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of widening of the diffraction peak attributable to a decline in the size of the grains is signified by β, while the Bragg angle is denoted by θ. 27,28 According to Table 2, the crystallization of PLA increased after orientation, but the crystal lattice size declined in conjunction with the draw ratio. T…”
Section: Crystallization Properties Analysismentioning
confidence: 99%